2015
DOI: 10.4236/ijcm.2015.69080
|View full text |Cite
|
Sign up to set email alerts
|

Pain and Radiographic Outcomes in Adult Idiopathic Scoliosis Patients Using a Scoliosis Activity Suit: An 18-Month Case Controlled Chart Review

Abstract: There are few conservative treatment options for patients with adult idiopathic scoliosis. These typically include pharmacologic pain management, epidural injections, and generalized CAM treatments such as massage and chiropractic manipulation. The purpose of this study was to compare the post-treatment results in patients wearing the scoliosis activity suit versus baseline assessments as well as adult scoliosis patients who did not wear the activity suit. The pain and Cobb angle outcomes of 53 consecutive pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…The 2 other studies were published by Morningstar et al 16,17 Both of these were case series studies in adult patients with a history of idiopathic scoliosis. In the first case series, Morningstar identified 62 patients who wore a scoliosis activity suit for 1 year and reviewed their pain and radiographic findings.…”
Section: Bracing Only (As Performed By Chiropractors)mentioning
confidence: 99%
See 1 more Smart Citation
“…The 2 other studies were published by Morningstar et al 16,17 Both of these were case series studies in adult patients with a history of idiopathic scoliosis. In the first case series, Morningstar identified 62 patients who wore a scoliosis activity suit for 1 year and reviewed their pain and radiographic findings.…”
Section: Bracing Only (As Performed By Chiropractors)mentioning
confidence: 99%
“…15 Morningstar et al did not follow skeletally immature patients through Risser 5, nor did they follow adult patients for the recommended 5 years. 16,17 …”
Section: Bracing Only (As Performed By Chiropractors)mentioning
confidence: 99%
“…Due to this rising occurrence in adult patients, investigation into scoliosis treatment for adults has been increasing [17]. Previous studies have reported pain and radiographic outcomes in patients wearing a scoliosis activity suit for various lengths of time [18] [19] [20]. The scoliosis activity suit is believed to cause a rotational stimulus which places a slow stretch on deep spinal muscles into the direction of scoliosis rotation, thus eliciting a corrective reflex that causes the same muscles to activate and result in counter-rotation of the spine out of the scoliosis pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Given that post-fusion patients still experience pain after surgery [7], adult patients are seeking more opportunities for pain management. Recently, Morningstar et al have published preliminary reports on a scoliosis activity suit for adult scoliosis treatment [8] [9]. They report both radiographic and pain improvements in adult patients wearing this suit for up to 18 months.…”
Section: Introductionmentioning
confidence: 99%